Growing pains : learning to love my father's faith - Balmer, Randall Herbert (Grand Rapids, Mich. : Brazos Press, 2001)
Many Christian families struggle with passing the faith from one generation to the next. In "Growing Pains, " Balmer addresses this issue in a series of beautifully crafted narrative essays. His engaging stories include everything from baseball to John Lennon to tidbits of Christian history. Ultimately, Balmer tells how he discovered the unconditional love of a heavenly father through grace, seeking, and identification with Jesus the Son.
Father, hear my cry: Faith of our fathers -- Generation of faith -- Christian piety through the generations -- Gospel and gossip -- Finishing the course -- Keeping faith -- discerning the call -- Sins of the fathers -- Family mMatters: Searching for grandpa -- Postcards -- My father's cars -- Passing of an era -- Some thoughts on attending a fifteen-year college reunion -- Eyes on the rencepost: Glimpses of grace --California dreamin' -- New York City, George Steinbrenner, and common grace -- Orange county journal -- Remembering John Lennon -- Silicon Valley -- Epilogue -- Eulogy -- Acknowledgments -- About the author.
Keywords: Balmer, Randall Herbert; Christian biography -- United States